PENGARUH DAYA LAMPU NEON TERHADAP PERTUMBUHAN TANAMAN PAK CHOI (Brassica rapa L.) PADA SISTEM HIDROPONIK INDOOR - Ning Hartati Setiasih; Sugeng Triyono; Ahmad Tusi; Diding Suhandy (The University of Lampung, 2016)
The purpose of this research was to observe the influence of neon lamp power (watt) on the growth of Pak Choiin an indoor hydroponic system. This research was done by implementing several pots of Pak Choi planting undersome different treatments of lighting. The treatment consisted of neon lamp 20 watt (N1), neon 2 x 20 watt (N2),neon 40 watt (N3), neon 2 x 40 watt (N4) in a growth chamber and one treatment under the sun lighting (N0).The result of the research showed that the treatment of 2 x 40 watt neon lamp (N4) turned out to have the bestresult at all variables measured. Then, it was followed by treatment of neon 40 watt (N3) and the lowest result wasin neon 20 watt (N1). The highest biomass harvested was 35 g in N4, followed by 18 g in N3, then the 15 g in N2and 4 g in N1. However, the highest ash content was in the treatment of 20 watt neon lamp (N1), and followed byN2 (neon 2 x 20 watt). Although, Pak Choi grown under the sun ray has the highest biomass harvested, but it hadthe lowest mineral content.Keywords : Neon lamp, lamp power, Pak Choi, hydroponic wick system